Fenomena Perceraian dan Perubahan Sosial: Studi Kasus di Kabupaten Wonosobo - Mahfudz Junaedi (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2018)
In the midst of the social changes that continue to occur today, divorces at Wonosobo increased high enough, it can even be said to occur on a massive scale.In general, the incedence of divorce are the root causes of the economic factor isthe ability of the husband in the household that evolved conention and strife that never cease. Divorce is more dominant from wives becouse of economic factors and strife. Another factor is that a third party (cheating), and lack of maturity, while KUA’s role as an institution has not been optimalized. The phenomenon of divorce can be changed if there is a systematic effort through education and public awareness about the importance of nurturing the love (sakinah, mawaddah, rahmah) in domestic life, because the actual prototype is located in the domestic life that is based on relationships loving, tolerant, appreciate differences.